Childhood psoriasis - Piekarska-Myślińska, Dorota; Pietrzak, Aldona; Myśliński, Wojciech; Pietrzak, Daniel; Borysowicz, Magdalena; Socha, Mateusz; Krasowska, Dorota (Dermatology Review/Przegląd Dermatologiczny, 2017)
Psoriasis is a long-lasting inflammatory skin disease with an autoimmunological and immunometabolic background. The latest European data indicate that the occurrence of psoriasis in children ranges from 0.7% to 2.1%. Despite distinct clinical characteristics, this disease continues to cause diagnostic difficulties and is often incorrectly diagnosed. The goal of this article is to present the course of psoriasis in children, basic diagnostic techniques, including dermoscopy, influence of the disease on the quality of life and risk of co-morbidity development. The therapeutic approcach to childhood psoriasis is presented.